2009
DOI: 10.1093/sleep/32.8.1049
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Sleep-Disordered Breathing and Sleep Symptoms with Change in Quality of Life: The Sleep Heart Health Study (SHHS)

Abstract: A slight increase in severity of sleep disordered breathing was seen over 5 years; this was not associated with worsening of quality of life. However, subjective symptoms of quality of sleep and daytime sleepiness were associated with declining quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 44 publications
3
61
3
1
Order By: Relevance
“…Previous studies show that when self-reported total sleep has been compared with sleep diaries, actigraphy, and polysomnography, there has generally been a good correlation between self-reported and objective measurements. 41,42 Second, information on change of the sleep profile was not able to be taken into account. Sleep duration and sleep quality might be changed during follow-up for some participants.…”
Section: 37mentioning
confidence: 99%
“…Previous studies show that when self-reported total sleep has been compared with sleep diaries, actigraphy, and polysomnography, there has generally been a good correlation between self-reported and objective measurements. 41,42 Second, information on change of the sleep profile was not able to be taken into account. Sleep duration and sleep quality might be changed during follow-up for some participants.…”
Section: 37mentioning
confidence: 99%
“…1 In recent years, a number of studies have indicated that sleep duration may be an important indicator of one's perceived health status. [2][3][4][5][6][7][8][9][10][11][12][13] Several studies also indicate that disorders of sleep duration hamper both perceived physical and mental health 4,5,9,[14][15][16] and report that perceived health risks in individuals with sleep durations are somewhat greater than those in individuals with chronic physical illness. 8,10 Moreover, both short and long sleep duration are associated with elevated risk of diabetes mellitus, hypertension, and cardiovascular disease (CVD).…”
mentioning
confidence: 99%
“…Sleep apnea is a serious, potentially life-threatening condition, characterized by repeated cessation of breathing while sleeping, due mostly to complete or partial pharyngeal obstruction [6,17]. Obstructive sleep apnea, the most prevalent of the sleep-disordered breathing constellation, has several cardio-respiratory features (e.g., loud snoring, loud gasps, and daytime breathlessness).…”
Section: Epidemiology Of Sleep Apneamentioning
confidence: 99%
“…[18][19][20]. Sleep apnea is also associated with a number of metabolic diseases [21][22][23][24][25][26][27][28], cardiac arrhythmias [18,19], cardiovascular disease [18,20], decreased quality of life [17] and early mortality [18,28]. It causes significant sleep disturbances and excessive daytime sleepiness [18,29], which often lead to road traffic and industrial accidents [18,27,30] as well as cognitive deficits and poor performance [31].…”
Section: Epidemiology Of Sleep Apneamentioning
confidence: 99%